Illegal immigration at sea: a social analysis (Imigraţia ilegală pe mare: o analiză socială) - Martina Federica MANFREDI (Polis: Revista de Stiinte Politice, 2014)
Illegal immigration could be defined as a pathology of migration (which is a much broader, positive and needed phenomenon). It is a phenomenon of relevant historical importance; in particular, European history has been marked by many waves of migration, sometimes of whole populations. Unfortunately, the problem of illegal immigration is still very much present in today’s society, touching certain countries in particular, such as Italy, which suffers immigration from sub-Saharan Africa and the Balkan area.